Antioxidant activity assay of white Turi (Sesbania grandiflora (L.) Pers.) extracts using DPPH radical scavenging method - Jamilatur Rohmah; Ida Agustini Saidi; Chylen Setiyo Rini; Zulfida Ainindiyah Putri Purwanto; Karlia Hedit Tiana; Tri Chahyani Rahmawati Putri (Universitas Ahmad Dahlan, 2020)
Turi (Sesbania grandiflora (L.) Pers.) is a type of plant belonging to the Fabaceae family that is widespread in Indonesian territory and has the potential as a natural free radical scavenger. The study aims to compare the antioxidant activity from white Turi (Sesbania grandiflora (L.) Pers.) leaf extracts in various extraction solvents. The determination of antioxidant activity was carried out using the DPPH method with a UV-Vis spectrophotometer. The turi plants used were originated from Mojosari, Mojokerto, East Java, Indonesia. Simplicia turi leaves were macerated in various extraction solvents: ethanol, ethyl acetate, and n-hexane for 24 hours. The extraction results are then subjected to phytochemical and antioxidant activity tests. The obtained result shows that the white turi extract has antioxidant activity with strong activity against DPPH radicals; with n-hexane > ethyl acetate extract > ethanol extract. The IC50 values of ethanol, n-hexane, and ethyl acetate extracts of white turi leaves were 33.09 ppm; 26.99 ppm; and 25.33 ppm. Based on these results, the white turi plant (leaves) can be one of the natural sources of antioxidants to prevent diseases caused by free radicals.